Determination to leaf and flower volatile components of natural sage taxa (Salvia Spp.) of Murat Mountain (Kütahya-Gediz) - İlkay ÖZDEK; Hüseyin FAKİR (Turkish Journal of Forestry, 2019)
In this study, it was aimed to determine volatile components in leaves and flowers in different collecting periods of sage (Salvia L.) taxa that have natural distribution in Mount Murat in Gediz district in Kütahya province. As result of field studies which were performed between 2016-2017, it was identified to distribution of Salvia verbenaca, Salvia verticillata, Salvia candidissima subsp. occidentalis, Salvia virgata, Salvia sclarea, Salvia frigida, Salvia bracteata taxa in this district. The aim of determining to volatile components, leaves and flowers were dried at room temperature and volatile components were detected by GC-MS equipment. In the end of analyses, 34 volatile components were detected for S. sclarea; 27 for S. candidissima subsp. occidentalis; 30 for S. verticillata; 39 for S. virgata; 33 for S. frigida; 31 for S. verbenaca and also 38 for S. bracteata. Main components were Linalyl acetate (%84,83), Linalool (%2,47) and β -Myrcene (%2,27) for S. sclarea, γ- terpinene (%28,76), Sabinene (%20,26) and Linalool (%11,26) for S. candidissima subsp. occidentalis, Benzofuran-2-one (%40,98), trans-Caryophyllene (%14,42), Geyrene (%8,43) and Methalactone (%) for S. verticillata, α-Pinene (%37,17), 2β-Pinene (%21,4) and Limonene (%10,85) for S. virgata, Linalyl acetate (%44,09), β-Myrcene (%9,26) and β-pinene (%7,87) for S. frigida, Linalyl acetate (%81,70), Linalool (%8,66) and β-Myrcene (%2,73) for S. verbenaca, Phenethyl alcohol (%39,93), α-Copaene (%8,75) and Sabinene (%7,03) for S. bracteata.